Teori Al Amwal dan Kaitannya dengan Transaksi Syariah Al Amwal Al Batiniyyah, Al Zahiriyah, Al Am, dan Al Khas - Robaiyadi Robaiyadi; Muhamad Zen (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi Islam Institut Agama Islam (IAI) Al-Azhaar Lubuklinggau, 2025)
This study aims to determine how the theory of al-amwal relates to sharia transactions al amwal in fiqh muamalah al batiniyyah, al zahiriyah, al am, and al khas. The author uses a research approach library research method, which is a method that uses library sources such as books related to muamalah fiqh, journals, research results, and others related to the research topic. Amwal is a very important role in human life so that Islam has also provided learning about amwal from various forms, both in understanding, position and function, obtaining property and its utilization. As for the results of this study that the theory of al amwal in muamalah fiqh is widely explained by the scholars of the essence of property put forward by the majority of scholars and Hanafiyah scholars. According to the majority of scholars the property is not only material but also includes the benefits of an object. However, Hanafiyah scholars argue that what is meant by treasure is only material.